Translational pharmacology: role and its impact - Kumar, Sumit; Sattigeri, Bhagya M. (International Journal of Research in Medical Sciences, 2018)
Translational Pharmacology is a newly evolved branch as an extension of clinical pharmacology. Translational Pharmacology aims to move the results of the molecular pharmacological research to the patient level, which is focussed on developing the new drug that correlates with the patient needs. The basic objective is to study the changing trends from experimental to clinical pharmacology. It also helps to gather data from the preclinical studies, so as to have accurate and effective dosing in the critical clinical trials. Thus, we can conclude that Translational Pharmacology tries to bridge the gap between the basic molecular research studies in pharmacology to the clinical trials. This also reduces the time and economic burden on research. Thus, it helps in translating the knowledge from the basic animal studies to the bedside patient studies.